Simulation and optimization of EMI filter of conducted emission for high voltage gain DC-DC converter - Ouhammam, Abdelaali; Mahmoudi, Hassane; El Hachimi, Youssef; Daghouri, Amina (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
In the continuity of the work on design of high voltage gain DC-DC converter, used for feeding the CubeSat electrospray thrusters with a variable output voltage according to the maneuver size, this paper introduces a simulation of the converter model with MATLAB/Simulink to determine its conducted emission level. By referring to the MIL-STD-461 standard, a required passive electromagnetic interference (EMI) filter parameters are calculated to reduce, under thresholds, the converter noise. With consideration of the available volume and power constraints in this kind of satellite, the design of common-mode (CM) choke is optimized with proposed procedure optimization, so as to reduce its volume and electrical losses. Also, this optimization procedure can be generalized and applied for any passive EMI filter design.